THE RIGHT TO VOTE AND BREACH OF VOTING SECRECY - Radu-Florin GEAMĂNU (Challenges of the Knowledge Society)
The article is meant to be a brief overview of the legal provisions concerning the right to vote, encompassing both the national provisions and the international standards. The scientific approach also includes the fixation of the standards in the field of the right to vote, as defined in the European Court of Human Rights case-law. Due attention will be granted to the provisions on the breach of voting secrecy, provided for in the current Criminal Code, which entered into force on the 1st of February 2014, as this piece of legislation regulates in a unified way the offence, applicable for any type of elections performed in Romania. The paper will focus, also, on the legislation of some European states, in order to assess the compatibility of the offence of breach of voting secrecy with similar offences in the legislation of other countries. To close with, the study will give some conclusions regarding the importance of the criminal punishment of the offence of breach of voting secrecy, as well as the conformity of this particular offence with the internationals standards.